System Design Tool for High Bit Rate Terrestrial Transmission Systems With Coherent Detection. (December 2013) - Lavigne, Bruno; Lefrançois, Mathieu; Balmefrezol, Elodie; Bresson, Christine; Vacondio, Francesco; Antona, Jean‐Christophe; Seve, Emmanuel; Rival, Olivier; Leven, Andreas; Varma, Eve L.
Abstract Coherent detection offers the ability to compensate for linear transmission impairments such as fiber chromatic dispersion and polarization‐mode dispersion in the digital domain, thereby enabling dispersion‐uncompensated optical transmission for high performance and high cost effectiveness. In dispersion‐uncompensated transmission systems, the statistics of optical nonlinearity induced distortions have been proven to be essentially Gaussian‐distributed, and new physical models have emerged showing profound differences with respect to legacy systems based on direct detection. From such differences stems the need to adapt the design tool to capture these new propagation properties. In that respect, we propose a model for performance prediction, which is used to derive a simple yet effective feasibility parameter to be embedded in the design tool. The feasibility parameter is experimentally validated with real time product transponders, and realistic system configurations: a precision of ±0.5 dB is achieved for 40 Gb/s, 100 Gb/s and 400 Gb/s coherent channels, which represents an improvement of more than 3 dB over the design tool using the nonlinear phase shift as the criterion. ©2013 Alcatel‐Lucent.